Desarrollo de un método verde para la oxidación de alcoholes utilizando alcohol bencílico como modelo - Villalobos, Karen (2019)
The oxidation of alcohols is an important reaction in the synthesis of aldehydes and ketones, two important raw materials in the chemical industry. The classic methods to perform this transformation have the disadvantage of using oxidizers in stoichiometrical amounts or higher, generating a lot of waste. Though several research groups have developed better methodologies, this problem remains unsolved. In this work we have developed a method for the oxidation of alcohols using a catalytic system based on Cu(OAc)2, H2O2 and using benzyl alcohol as the oxidation probe. The reaction conditions were optimized and it was found that using 0.5 mol % of the catalyst in acetonitrile for 24 hours at 40 ºC gives acceptable isolated yields with a selectivity of 73% in favor of the aldehyde. It was also found that the selectivity of the reaction can be changed in favor of the carboxylic acid when acetone is used as the solvent.